Grafting Islets to a Dissected Peritoneal Pouch to Improve Transplant Survival and Function. Issue 11 (November 2020) - Kumano, Kenjiro; Vasu, Srividya; Liu, Yang; Lo, Su-Tang; Mulgaonkar, Aditi; Pennington, Jenelle; Darden, Carly M.; Sun, Xiankai; Lawrence, Michael C.; Naziruddin, Bashoo
Abstract : Background: Although the liver is the primary site for clinical islet transplantation, it poses several restrictions, especially limited tissue volume due to portal vein pressure. We evaluated the preperitoneal space as an extrahepatic islet transplant site to deliver high tissue volumes and sustain long-term graft function. Methods: A peritoneal pouch was formed by dissecting the parietal peritoneum from the transversalis fascia of mice. Syngeneic C57BL/6 donor islets were transplanted into the peritoneal pouch of diabetic mouse recipients. Blood glucose was monitored for islet function, and miR-375 was analyzed for islet damage. Islet graft morphology and vascularization were evaluated by immunohistochemistry. [ 18 F] fluoro-D-glucose positron emission tomography/computed tomography was used to image islet grafts. Results: Transplantation of 300 syngeneic islets into the peritoneal pouch of recipients reversed hyperglycemia for >60 days. Serum miR-375 was significantly lower in the peritoneal pouch group than in the peritoneal cavity group. Peritoneal pouch islet grafts showed high neovascularization and sustained insulin and glucagon expression up to 80 days posttransplantation. A peritoneal pouch graft with high tissue volume (1000 islets) could be visualized by positron emission tomography/computed tomography imaging. Human islets transplanted into the peritoneal pouch of diabetic nude mice also reversed hyperglycemia successfully. Conclusions: Islets transplanted into a dissected peritoneal pouch show high efficiency to reverse diabetes and sustain islet graft function. The preperitoneal site has the advantages of capacity for high tissue volume, enriched revascularization and minimal inflammatory damage. It can also serve as an extrahepatic site for transplanting large volume of islets necessitated in islet autotransplantation. Abstract : Supplemental Digital Content is available in the text.